2022
DOI: 10.3389/fped.2022.921863
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Point-of-Care Ultrasound in Acutely and Critically Ill Children (POCUS-ped): A Scoping Review

Abstract: IntroductionPoint-of-care ultrasound (POCUS) use is increasing in pediatric clinical settings. However, gastric POCUS is rarely used, despite its potential value in optimizing the diagnosis and management in several clinical scenarios (i.e., assessing gastric emptying and gastric volume/content, gastric foreign bodies, confirming nasogastric tube placement, and hypertrophic pyloric stenosis). This review aimed to assess how gastric POCUS may be used in acute and critically ill children.Materials and MethodsAn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…17 However, plain abdominal radiography still needs to be improved in making the diagnosis. 18 A review by Valla et al 19 showed that, compared to x-ray, gastric POCUS could be used to confirm the presence of a foreign body. This is due to the low efficacy of plain abdominal radiography, especially in detecting the presence of a nonradio-opaque foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, plain abdominal radiography still needs to be improved in making the diagnosis. 18 A review by Valla et al 19 showed that, compared to x-ray, gastric POCUS could be used to confirm the presence of a foreign body. This is due to the low efficacy of plain abdominal radiography, especially in detecting the presence of a nonradio-opaque foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric point of care ultrasound (POCUS) is another non-invasive technique with wider potential applicability in the ICU. Gastric US has been studied in healthy pediatric cohorts, the perioperative setting, and in premature and full-term neonates [ 40 ]. Assessments of gastric contents, gastric volume, and the antral cross-sectional area have all been considered [ 40 ].…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…Gastric US has been studied in healthy pediatric cohorts, the perioperative setting, and in premature and full-term neonates [ 40 ]. Assessments of gastric contents, gastric volume, and the antral cross-sectional area have all been considered [ 40 ]. Fewer studies have been performed in the pediatric ICU.…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…14 A scoping review of gastric POCUS in children mentions the potential for emergency physicians to diagnose intragastric tricobezoar with POCUS. 15 However, there are no cases to date demonstrating the utility of POCUS for diagnosis of a gastric trichobezoar in a pediatric patient. Ultrasound diagnosis of bezoars in the pediatric population is especially important to limit exposure to radiation from other radiographic modalities including barium studies and CT scans.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There have been several cases in the literature demonstrating the utility of ultrasound for diagnosis of trichobezoars by radiologists, 1,9,11–13 and ultrasound has also been used in a Gastroenterology Unit to confirm the diagnosis in a 20-year-old patient with a history of trichophagia presenting with vomiting and abdominal pain 14 . A scoping review of gastric POCUS in children mentions the potential for emergency physicians to diagnose intragastric tricobezoar with POCUS 15 . However, there are no cases to date demonstrating the utility of POCUS for diagnosis of a gastric trichobezoar in a pediatric patient.…”
Section: Review Of Literaturementioning
confidence: 99%